Intervención de los niveles Fonológicos y Lexicales del lenguaje en un usuario con TEL.: - Guadrón Navarro, Susana (2020)
Because there is a high rate of children with Specific Language Disorders (TEL), where phonological and lexical levels are affected, which produces poor vocabulary, as well as difficulties in not being able to properly understand or express the content of meaning of its language, we are in need of carrying out the present study that is called “Intervention of the phonological and lexical levels of language in a user with TEL, case study” which has as main objective to establish if changes are obtained in the understanding and expression of concepts and relationships of meaning, when working the phonological and lexical levels within a case with Specific Language Disorder. The present work is a case study of qualitative and descriptive type design, because only main characteristics or components will be described, the research design corresponds to a transversal type strategy, since the variables are studied simultaneously in a short period of time The population under study in this research consists of a four-year-old male user with Specific Language Disorder. Regarding the conclusions, it can be pointed out that there was an increase in the scores of all language levels, placing the child in a severe delay, in a more favorable position of moderate delay, which proves that with the direct intervention of the phonological and lexical component. semantics if improvement was observed.